Unveiling the potential impact of RNA m5C methyltransferases NSUN2 and NSUN6 on cellular aging - Zhou, Jiale; Han, Yang; Ji, Fuxi; Zhang, Renquan; Liang, Yuru; Zhao, Xudong; Hou, Ruizhe (Frontiers in Genetics, 2025)
NSUN2 and NSUN6, two family members of NOL1/NSUN protein, are mainly responsible for catalyzing the formation of 5-methylcytosine (m5C) in RNA and highly involved in the physiological and pathological processes of many diseases. To investigate the biological functions of NSUN2 and NSUN6, NSUN2−/− and NSUN6−/− HEK293T cell lines were separately constructed by CRISPR/Cas9. We found no significant interaction between the protein expression of NSUN2 and NSUN6. Notably, the ablation of NSUN2 or NSUN6 reduced cell proliferation and increased expression of the senescence-associated marker P27, whereas more β-galactosidase-positive cells were observed in response to H2O2-induced oxidative stress. Moreover, the expression of NSUN2 and NSUN6 was significantly reduced in the HGPS premature aging cell lines by the LMNAG609G mutation. Taken together, we demonstrated that NSUN2 and NSUN6 may be inextricably linked to cellular aging and thus provide potential novel strategies for the clinical therapeutics of aging and age-associated disease in the future.